High‐Abundance and Low‐Cost Metal‐Based Cathode Materials for Sodium‐Ion Batteries: Problems, Progress, and Key Technologies. Issue 14 (21st February 2019) - Chen, Mingzhe; Liu, Qiannan; Wang, Shi‐Wen; Wang, Enhui; Guo, Xiaodong; Chou, Shu‐Lei
Abstract: Recently, room‐temperature stationary sodium‐ion batteries (SIBs) have received extensive investigations for large‐scale energy storage systems (EESs) and smart grids due to the huge natural abundance and low cost of sodium. The SIBs share a similar "rocking‐chair" sodium storage mechanism with lithium‐ion batteries; thus, selecting appropriate electrodes with a low cost, satisfactory electrochemical performance, and high reliability is the key point for the development for SIBs. On the other hand, the carefully chosen elements in the electrodes also largely determine the cost of SIBs. Therefore, earth‐abundant‐metal‐based compounds are ideal candidates for reducing the cost of electrodes. Among all the high‐abundance and low‐cost metal elements, cathodes containing iron and/or manganese are the most representative ones that have attracted numerous studies up till now. Herein, recent advances on both iron‐ and manganese‐based cathodes of various types, such as polyanionic, layered oxide, MXene, and spinel, are highlighted. The structure–function property for the iron‐ and manganese‐based compounds is summarized and analyzed in detail. With the participation of iron and manganese in sodium‐based cathode materials, real applications of room‐temperature SIBs in large‐scale EESs will be greatly promoted and accelerated in the near future. Abstract : State‐of‐the‐art high‐abundance and low‐cost metal‐based cathode materials for sodium‐ion batteries are comprehensively summarized and analyzed, providing a step toward the real‐life, commercial application of sodium‐ion batteries. Constructive suggestions and guidance are provided and future prospects regarding this promising field are discussed.